Computational studies on the water‐catalyzed stereoinversion mechanism of glutamic acid residues in peptides and proteins. Issue 5 (12th March 2018) - Nakayoshi, Tomoki; Kato, Koichi; Fukuyoshi, Shuichi; Takahashi, Ohgi; Kurimoto, Eiji; Oda, Akifumi
Abstract: In contrast with the common belief that all the amino acid residues in higher organisms arel ‐forms, d ‐amino acid residues have been recently detected in various aging tissues. Aspartic acid (Asp) residues are known to be the most prone to stereoinvert via cyclic imide intermediate. Although the glutamic acid (Glu) is similar in chemical structure to Asp, little has been reported to detectd ‐Glu residues in human proteins. In this study, we investigated the mechanism of the Glu‐residue stereoinversion catalyzed by water molecules using B3LYP/6‐31+G(d, p) density functional theory calculations. We propose that the Glu‐residue stereoinversion proceeds via a cyclic imide intermediate, i.e., glutarimide (GI). All calculations were performed by using a model compound in which a Glu residue was capped with acetyl and methylamino groups on the N ‐ and C ‐termini, respectively. We found that two water molecules catalyze the three steps involved in the GI formation: iminolization, cyclization, and dehydration. The activation energy required for the Glu residue to form a GI intermediate was estimated to be 32.3 kcal mol −1, which was higher than that of the experimental Asp‐residue stereoinversion. This calculation result suggests that the Glu‐residue stereoinversion is not favored under the physiological condition. Abstract :